Pemanfaatan material cork untuk desain kemasan parfum - Melatitanica Arkarima; ‪Mochamad Junaidi Hidayat (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2021)
Cork is an environmentally friendly material, has unique properties and characteristics, but in Indonesia Cork is only used as a material coaster and Cork Board products. Therefore, there appears an idea to develop a product of perfume packaging with cork material, because the perfume packaging is only box-shaped and cylinder. In this study, the collection of data used is by means of surveys and interviews, and assisted with supporting data such as secondary data (books, journals, Internet). Case studies conducted on this research conducted on five objects, namely PT. Grafika Prima Sejahtera, CV. Mulia Jaya Box, PT. Universal artwork, Cote De Azuro perfume Store and Victoria's Secret perfume Shop. The analysis used is an experimental analysis, before analyzing the design of competitors ' bottles and perfume packaging as part of the experimental step, researchers divided several stages of the experiment, the material stage, the coloring stage, Management stage, finishing stage, form experiment and material mix. Concept used is the concept of duplicate, namely following the form of perfume bottles and iconic, namely using the shape icons of women's body, to show perfume used in women. The duplicate concept is used on brands such as Bleau De Chanel perfume, Chanel Chance Women, Silver Babe Park Lane and Victoria's Secret. Iconic concept used on brand perfume Bvlgari Omnia. Researchers made 5 design alternatives, 4 with duplicate and 1 concepts with iconic concepts.